On the shore of Mediterranean sea. The end of the palaeolithic on the coast of Málaga (South of Spain). - Cortés-Sánchez, Miguel; Calle Román, Lidia; Simón-Vallejo, M. Dolores; Lozano-Francisco, María del Carmen; Riquelme-Cantal, José A.; Vera-Peláez, José L.; Parrilla Giráldez, Rubén; Macias Tejada, Sara (Elsevier Ltd and INQUA, 2019)
The coast of Málaga constitutes a key territory for documenting the end of Palaeolithic times in the westernmost corner of the European continent. We present an overview of the economic, cultural and symbolic models documented in settlements from this region. Along with it, some of the main questions that will help to frame the research in this area are set out. Lastly, the use of the coastal fringe is discussed from the standpoint of mobility and economic strategies from southern Iberia, taking into account the hinterland and Guadalquivir basin territories.
Keywords: Magdaleniense; Neolítico; Southern Iberia; Magdalenian; Neolithic; Settlement Subsistence; Symbolism